ANALISIS KAPASITAS JALAN DENGAN METODE TRAFFIC MICROSIMULATION - Pribadi, Ocky Soelistyo; Munawar, Ahmad; Malkamah, Siti (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The using of Indonesian Highway Capacity Manual (IHCM) for road capacity and traffic speed analysis need to be reconsidered, because of the old-fashioned basic data. There are increasing of elements like the quantity of motorbike and their compotition ini traffic and the increasing of national road length, bring to the condition that the Indonesia’s traffic characteristics is now changing. IHCM formed by the using of macroscopic traffic flow theory, this study uses microscopic side, implementing traffic simulation with helped of Vissim software on Menteri Supeno Road in Yogyakarta at 6.45 am to 7.45 am. The statistics analysis on the distribution of vehicle arrival headway and traffic speed, told that there is no significant difference between the survey and the Vissim’s result, the analysis continued, found that the capacity of the road is 4,193 vehicles.